Možnosti uplatňování veřejných politik aftercare v České republice - Stejskal, Jan; Charbuský, Miloš (Univerzita Pardubice, 2007)
Foreign direct investment (FDI) plays an important role in the development of some regions. In last years the number of new FDI projects has decreased and therefore the countries and regions pay more attention to their present investors to keep them in their country or region. This kind of services is called after-care services. The main provider of after-care services in the Czech Republic is the government agency CzechInvest which provides incentives and other programmes for foreign investors. Using incentives for expansions has increased during last years and almost one third of them were also used for uprading of plant status (creation of technological centres or centres of strategic services). Expansions are concentrated mainly in the Central Bohemia, especially in Prague metropolitan area, while the attraction of other metropolitan areas is not so strong.Relevant number of expansions and new created jobs is located in the problem regions with more favourable incentives. These findings prove that the programmes of CzechInvest FDI and their expansions is influenced to some extent by the programmes of CzechInvest which provide more support to less favoured regions. The expansions with uprading of plant status are located rather in regions with higher quality of human resources. Most of expansions (including expansions with upgrading of plant status) are located at the same place as the former investment project. CzechInvest provides only limited number of programmes for increasing level of embeddedness in the regional economy and that is the reason why the impacts of these programmes are rather insignificant.

Foreign direct investment (FDI) plays an important role in the development of some regions. In last years the number of new FDI projects has decreased and therefore the countries and regions pay more attention to their present investors to keep them in their country or region. This kind of services is called after-care services. The main provider of after-care services in the Czech Republic is the government agency CzechInvest which provides incentives and other programmes for foreign investors. Using incentives for expansions has increased during last years and almost one third of them were also used for uprading of plant status (creation of technological centres or centres of strategic services). Expansions are concentrated mainly in the Central Bohemia, especially in Prague metropolitan area, while the attraction of other metropolitan areas is not so strong.Relevant number of expansions and new created jobs is located in the problem regions with more favourable incentives. These findings prove that the programmes of CzechInvest FDI and their expansions is influenced to some extent by the programmes of CzechInvest which provide more support to less favoured regions. The expansions with uprading of plant status are located rather in regions with higher quality of human resources. Most of expansions (including expansions with upgrading of plant status) are located at the same place as the former investment project. CzechInvest provides only limited number of programmes for increasing level of embeddedness in the regional economy and that is the reason why the impacts of these programmes are rather insignificant.
Keywords: Podpora podnikání; Investiční pobídky; ekonomické podmínky; CzechInvest; Česká Republika; veřejná správa